Do high-performance work systems mediate the relationship between HR practices and employee performance in multinational corporations (MNCs) in developing economies? - Abugre, J.B.; Nasere, D. (African Journal of Economic and Management Studies, 2020)
Purpose – The purpose of this paper is to examine the mediating role of job involvement as high-performance work system (HPWS) on the relationship between human resource (HR) practices and employee performance in multinational corporations (MNCs) in developing economies using Ghana as a case study. Design/methodology/approach – Using questionnaires to collect data from 317 employees and ten MNCs in Ghana, structural equation modeling (SEM), multiple regression and bootstrapping analysis were used to analyze the data. Findings – The results showed that an HPWS proxy as job involvement fully mediates the relationship between HR practices and employee performance. The findings also showed that training and development and compensation and reward have a significant and direct positive effect on employee performance. Practical implications – This paper provides a practical guide to management and corporations on the significance of training and compensation on employee performance in MNCs. The study, therefore, recommends managers of firms and corporations to take a serious look at their HR practices and institute an HPWS, which can positively improve both corporate and employee performance. Originality/value – This paper enhances our understanding of micro-level HPWS in the form of job involvement as a positive mediator between training and development and employee performance on the one hand, and between compensation and reward and employee performance on the other hand in work organizations in a less-studied context.
Research Article
Keywords: HR practices; Employee performance; Job involvement; High-performance work system